An overview on the green synthesis and removal methods of pyridaben - Chen, Lingzhu; Pan, Mengyuan; Hu, Deyu (Frontiers in Chemistry, 2022)
Pyridaben is an acaricide widely used around the world to control phytophagous mites, white flies, aphids, and thrips. It is highly toxic to nontarget organisms such as predatory mites, bees, and fishes. Therefore, the occurrence and removal of pyridaben in food and the environment are worthy of concern. This mini-review focuses on pyridaben residue levels in crops, aquatic systems, and soils, as well as the green synthesis and removal of pyridaben. During the period of 2010–2022, pyridaben was reported in monitoring studies on fruits, vegetables, herbs, bee products, aquatic systems, and soils. Vegetable and agricultural soil samples exhibited the highest detection rates and residue levels. One-pot synthesis offers a green chemistry and sustainable alternative for the synthesis of pyridaben. Among traditional home treatments, peeling is the most effective way to remove pyridaben from crops. Magnetic solid-phase extraction technology has emerged as a powerful tool for the adsorption and separation of pyridaben. Photocatalytic methods using TiO2 as a catalyst were developed as advanced oxidation processes for the degradation of pyridaben in aqueous solutions. Current gaps in pyridaben removal were proposed to provide future development directions for minimizing the exposure risk of pyridaben residues to human and nontarget organisms.